Complexos interpolieletrolíticos de quitosana e poli (4-estireno sulfonato de sódio): preparação, caracterização e aplicação na adsorção de fármacos - Lima, Camila Renata Machado de (2016)
Oppositely charged polyelectrolytes interact electrostatically to form the so-called interpolyelectrolyte complexes (IPEC’s). By combining different types of polyelectrolytes, different structures may be formed, which makes necessary the physicochemical characterization of these interpolyelectrolyte complexes. Thus, in this study, initially, were obtained interpolyelectrolyte complexes between chitosan and poly (4-styrene sulfonate of sodium) at different molar ratios, rSA (sulfonate/aminium), by simply mixing the solutions of these polyelectrolytes in acid medium: it is the chitosan as the polycation and poly (4-styrene sulfonate of sodium) as the polyanion. Thereafter, the IPEC’s were characterized by measurements of viscosity, turbidity, conductivity, zeta potential, beyond techniques the dynamic light scattering (DLS) and scattering X-ray small angle (SAXS). The wide range of seventeen molar ratios, rSA (0.01; 0.03; 0.05; 0.1; 0.2; 0.3; 0.4; 0.5; 0.6; 0.7; 1.4; 1.7; 2.0; 2.5; 3.3; 5.0 e 10), investigated in this work generated colloidal particles of lyophilic and liophobic nature. The turbidity and conductivity measurements showed a drastic increase when the molar ratio had its value equal 1. The zeta potential in this region rSA = 1 was 0, confirming the neutral charge and a 1:1 stoichiometry between the polyelectrolytes. From the parameters obtained by DLS and SAXS it was possible to characterize the process of formation of IPEC’s. The solid particles obtained IPEC’s were characterized by TG, DRX and FTIR, indicating that complexation polyelectrolytic inhibited the occurrence of crystalline regions. Subsequently, experiments were conducted to monitor and characterize the adsorption process of two drugs, tetracycline and cromoglycate, in solid particulate IPEC’s derived from two different molar ratios, rSA = 0.7 e 1.43. Adsorption isotherms and a kinetic model were used in the experimental data to describe the adsorption process. The particles IPEC’s obtained from the rSA = 0.7 and rSA = 1.43 appeared to be good adsorbents for tetracycline. However, no adsorption process of the cromoglycate in particles obtained from the rSA = 1.43 was observed.